Euronet Lab : a Cloud Based Laboratory Environment - Correia, Raúl Cordeiro (2014)
A large number of virtual and remote labs connected to the internet is already available nowadays. However, they usually are isolated and independent systems, unable to cooperate and complement each other. This lack of interconnection and interoperability leads, consequently, to the duplication of efforts in order to develop what could be easily shared and reused. Therefore, the integration of different platforms can speed up the development of virtual labs and downsize the barriers of using complementary systems that would represent an unachievable development task. In this paper one presents a proposal for the implementation of an open system that will be able to integrate different virtual lab platforms and components by interconnecting them and establishing communication mechanisms that will support understanding and agreement between heterogeneous systems. When one tries to interconnect systems developed on geographically distant places, often using different languages and different cultures, obstacles may arise. In this paper we present a proposal for a new system that allows users to do exactly this; to interconnect several virtual and remote labs through the internet, and to perform tests using components of several of these systems even if they are physically separated from each other.